Decoupling Control Applied to the Smart Grid Power Dispatching Problem - Nebili, S.; Benabdallah, I.; Cherif, A. (Engineering, Technology & Applied Science Research, 2022)
This paper presents controller designs of the decoupling issue dedicated to renewable decentralized generators or new generation grids known as smart grids. The control methods were based on a three-phase voltage source grid representation that integrated wind and photovoltaic generators. The utilized decoupling strategies (Boksenbom and Hood, Zilkind and Luyben, and inverted decoupling) allowed the optimization of energy transfers and costs through the routing grid distribution path. Simulations were conducted in Matlab/Simulink. The trustworthiness of the multivariable control system design in addition to the tuning method was established using three test batches, totally decoupled and stable from input dependencies.